Environmental systems and societies course companion - Rutherford, Jill; Williams, Gillian (Education director) (Oxford IB diploma programme, 2015)
rther reading, resources. 520 __ a "Motivating learners to explore and investigate scientific concepts, this new core Course Book helps learners actively connect study with wider issues relevant to the world today. The most comprehensive match to the 2015 syllabus and the only DP Environmental Systems developed with the IB, the inquiry-based approach truly engages learners. Features: Truly engage learners with scientific concepts - the inquiry-based approach drives active exploration, investigation and critical thought. Fully cover the new syllabus - the most comprehensive support for the new syllabus (first examination 2017), developed directly with the IB. Strengthen achievement - current case studies and activities accessibly connect learning with relevant global issues, driving motivation and achievement. Accurately implement the new requirements- written by DP Curriculum Developers and authors of the new syllabus. Support the new internal assessment - fresh ideas and new approaches to practicals from Gillian Williams help you tackle the changes. Build assessment potential - assessment support directly from the IB provides unrivalled exam preparation. Also available as an Online Course Book."--Publisher's website.